The Challenges of Personal Data Protection Policy in Indonesia: Lesson learned from the European Union, Singapore, and Malaysia - Ramadhan, Kiki Rezki; Wijaya, Chandra (Technium Social Sciences Journal, 2022)
Cases of leakage of personal data are a serious problem for countries that should be guaranteed safety as the identity and rights of individual citizens. In Indonesia, there are still many problems related to the security of cyberspace, one of which is becoming a trend of public issues, namely leakage of personal data. The rapid development of information and communication technology has provided changes to the character of community activities that are currently dominated by the use of the internet as a characteristic of modern society so the presence of the state to provide protection is important for the community. In this article, a case study of data leakage incidents in Indonesia and personal data protection policies carried out in the European Union, Singapore and Malaysia were chosen to be presented. The European Union is a supranational organization that has successfully implemented a policy of protecting personal data through the General Data Protection Regulation (GDPR). Meanwhile, Singapore has implemented a similar policy since 2012 through Personal Data Protection Act. Other learning can also be taken from Malaysia which already has a national regulation on data protection since 2010. Indonesia needs to take lessons by conducting policy comparative analysis and can contribute to the government in making derivative regulations from the newly ratified personal data protection law by the House of Representatives of the Republic of Indonesia to provide concrete protection for personal data in Indonesia.